Forecast of Commodity Energy Consumption and Structure of Rural Households in Sichuan Province - Wu, Wenzhi (International Journal of Electric Power and Energy Studies, 2024)
With the growth in energy consumption, problems such as environmental pollution and resource depletion are becoming more and more prominent, and the sustainable use of energy resources and sustainable economic and social development can be achieved only through scientific forecasting and effective management. Forecasting the changing trend of energy consumption structure can guide the government and society to take corresponding measures for environmental protection and sustainable development, and reduce the negative impact of energy consumption on the environment. Based on the current development situation of commodity energy in rural households in Sichuan Province and related consumption data, this paper uses the grey prediction model and Markov model to predict the consumption and consumption structure of commodity energy in rural households in Sichuan Province. It is found that among the four types of commodity energy consumed by rural households in Sichuan Province, the consumption of electricity shows exponential and growth, and it is expected that the consumption of electricity by rural households in Sichuan Province from 2022 to 2025 will be 3,316,166, 3,582,203, 3,886,622, and 4,216,240 tonnes of standard coal, respectively. Meanwhile, using Markov chain to predict the consumption structure, it is found that under the no-planning constraint scenario, the share of energy consumption of electricity and natural gas is increasing, while the share of energy consumption of coal and liquefied petroleum gas (LPG) will be decreasing, and the shares of energy consumption of coal, electricity, natural gas, and LPG will be 1.97 per cent, 75.82 per cent, 26.36 per cent, and 0.02 per cent, respectively, by 2030.